Package modular-thm: Properties of modular arithmetic

Information

namemodular-thm
version1.20
descriptionProperties of modular arithmetic
authorJoe Hurd <joe@gilith.com>
licenseMIT
provenanceHOL Light theory extracted on 2012-02-10
requiresbool
natural
modular-def
showData.Bool
Number.Modular
Number.Natural

Files

Theorems

fromNatural modulus = 0

x. toNatural x < modulus

~0 = 0

x. ~~x = x

x. x + 0 = x

x. 0 + x = x

x. toNatural x div modulus = 0

x. x * 0 = 0

x. x + ~x = 0

x. 0 * x = 0

x. ~x + x = 0

x. toNatural x mod modulus = toNatural x

x. x * 1 = x

x. 1 * x = x

x y. x * y = y * x

x y. x + y = y + x

x. fromNatural x = 0 divides modulus x

x. ~x = 0 x = 0

x y. x < y toNatural x < toNatural y

x y. x * ~y = ~(x * y)

x y. ~x * y = ~(x * y)

x y. ~x = ~y x = y

x y. toNatural x = toNatural y x = y

x y. x + y = x y = 0

x y. y + x = x y = 0

x y. ~x + ~y = ~(x + y)

x y. toNatural (x * y) = toNatural x * toNatural y mod modulus

x y. toNatural (x + y) = (toNatural x + toNatural y) mod modulus

x y z. x * y * z = x * (y * z)

x y z. x + y + z = x + (y + z)

x y z. x + y = x + z y = z

x y z. y + x = z + x y = z

x y. fromNatural x = fromNatural y x mod modulus = y mod modulus

x y z. x * (y + z) = x * y + x * z

x y z. (y + z) * x = y * x + z * x

Input Type Operators

Input Constants

Assumptions

modulus mod modulus = 0

0 mod modulus = 0

t. (x. t) t

() = λp. p = λx.

x. fromNatural (toNatural x) = x

n. 0 * n = 0

n. 0 + n = n

n. n mod modulus < modulus

m. 1 * m = m

() = λp q. p q p

x. toNatural (fromNatural x) = x mod modulus

x. ~x = fromNatural (modulus - toNatural x)

m n. m * n = n * m

m n. m + n = n + m

m n. m < n m n

n. divides modulus n n mod modulus = 0

n. n mod modulus mod modulus = n mod modulus

x y. x < y ¬(y x)

m n. ¬(m n) n < m

() = λp q. (λf. f p q) = λf. f

x y. x y toNatural x toNatural y

m n. m < n m div n = 0

m n. m < n m mod n = m

x1 y1. fromNatural (x1 * y1) = fromNatural x1 * fromNatural y1

x1 y1. fromNatural (x1 + y1) = fromNatural x1 + fromNatural y1

m n. n m m - n + n = m

m n p. m * (n * p) = m * n * p

m n p. m + (n + p) = m + n + p

m n p. m * (n + p) = m * n + m * p

m n p. (m + n) * p = m * p + n * p

m n. m mod modulus * (n mod modulus) mod modulus = m * n mod modulus

m n. (m mod modulus + n mod modulus) mod modulus = (m + n) mod modulus